R.E.S Three / Rohani Mohd Dol ... [et. al] - Mohd Dol, Rohani; Zaidi, Sofi Sofhia; Thomas Tarang, Ezryn Vyvy; Ahmad, Syafina; Kamuri, Siti Hajar (2017)
The business plan of RES3 is proposed so that it can be taken by comprehensive manner. This business plan can give us the opportunity to have our own business in the future. This business is form of selling Hijab which consist five (5) shareholders. All shareholders had agreed about the capital, contributions, loss and profit of the business. We choose this business because of it shows every Muslim girl can wear their Hijab base in their wants. Besides that, no one will decimate as the profits and losses will be divided equally among the shareholders. The financial manager will announce whether the business will gain how much profits or losses at the end of the year. The partnership is the best way for us to involve in because of the shareholders will always sharing their ideas or even knowledge in order to get profits. In the other hand, we also can achieve high productive from time to time.